Enhancing Cybersecurity Through Intelligent Conversations : A Chatbot Approach - Asoke Nath; Prashant Gomes; Sanchita Paul (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Retrieval-based chatbots are fundamental tools in computer-mediated conversations. They use stored responses to act as virtual assistants, facilitating smooth interactions between users and computers. This examination investigates into how these chatbots work, emphasizing their crucial role in modern communication. They not only enable human-like interactions but also establish strong question-answer systems. Additionally, their ability to adapt to different contexts and user queries makes them invaluable in today's digital landscape. In a world where communication patterns are constantly evolving, retrieval-based chatbots are essential for bridging gaps in understanding and improving human-computer interaction. They excel at interpreting and responding to queries across various fields, from customer service to education. As technology advances, retrieval-based chatbots will continue to shape the future of conversational interfaces, providing dynamic platforms for interacting with machines. Their significance in digital communication is bound to increase, setting their status as indispensable assets in the technological landscape.
Keywords: Retrieval-Based; Chatbot; Cybersecurity; Natural Language Processing; Deep Learning; Pattern Recognition; Contextual Understanding